Temperature-resilient performance of hemp rope–Confined recycled aggregate concrete in axial compression - Thansirichaisree, Phromphat; Ejaz, Ali; Chaimahawan, Preeda; Hussain, Qudeer; Jirasakjamroonsri, Amornthep; Saingam, Panumas (My University, 2026)
This study addresses the growing need for sustainable and cost-effective alternatives to conventional fiber-reinforced polymer (FRP) confinement systems, particularly for recycled aggregate concrete (RAC) subjected to elevated temperatures. The axial compressive behavior of hemp rope-confined RAC cylinders was experimentally investigated under ambient and moderate thermal exposure (150°C). Two strength grades were considered, with confinement applied using one to three layers of hemp rope. The results demonstrate that hemp confinement significantly enhances both compressive strength and axial strain, with improvements increasing with the number of layers, while strain enhancement was consistently more pronounced than strength gain. The stress–strain response exhibited a characteristic two-stage behavior, consisting of an initial unconfined-like region followed by a confinement-activated ascending branch. The elastic modulus of RAC was found to be approximately 21.9% to 29.7% lower than ACI 318-19 predictions, suggesting a reduction factor of about 25% for practical applications. Thermal exposure had a limited effect on normalized strength and strain parameters, although post-peak stiffness showed some sensitivity. Notably, confinement proved even more effective in thermally damaged specimens due to increased lateral deformability. A regression-based analytical model was developed to predict the complete stress–strain response, showing close agreement with experimental results. This study is among the first to evaluate the performance of hemp rope confinement for RAC under elevated temperature conditions and to propose a unified predictive framework. Overall, the findings confirm that hemp rope confinement is an effective, sustainable, and reliable technique for enhancing both the strength and ductility of RAC, with strong potential for structural applications, including post-fire rehabilitation.
Keywords: Analytical modeling; Fire exposure; Hemp confinement; Recycled aggregate concrete